SUSTAINABLE GREEN BUILDING INITIATIVES IN MALAYSIA: ISSUES IN THE IMPLEMENTATION PRACTICES - Zakaria, Zuhaila; Muhamad Ariff, Nor Rima; Ahmad Noorhani, Nur Maizura; Hussain, Mohd Mawardi (PLANNING MALAYSIA, 2024)
In recent years, green building practices have received tremendous global attention for their ability to protect the environment and foster sustainable development, and Malaysia, one of the fastest-growing countries, is enthusiastically embracing the green building movement. However, throughout the construction period of this green building, many issues occurred that contributed to the deterioration of the performance of the building itself. This research aims to identify the main issues faced by green building projects in Malaysia to ensure the performance of the building can be maintained and improved, by using a questionnaire survey that collects the views of 72 experienced participants. The findings reveal that operation and maintenance are urgent issues that need to be addressed in Malaysian green building projects, underscoring the need for policy intervention. Overall, this study can support the regulation of green building maintenance, underlining the critical nature of recognizing and addressing these issues collectively to foster the growth and success of green building initiatives in the Malaysian construction industry, thereby contributing to a more sustainable construction environment throughout the country.